UPAYA THE OCEAN CLEANUP DALAM MENANGGULANGI THE GREAT PACIFIC GARBAGE PATCH (GPGP) - Cahyani, Annisa Febri; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research describes the effort of an NGO named the Ocean Cleanup in overcoming plastic waste in the Great Pacific Garbage Patch (GPGP). The efforts are made by cleaning GPGP and polluted rivers. This activity is carried out with the support and network provided by partners. The research utilized the Theory of the Role of Environmental NGOs to analyze the role of the Ocean Cleanup. The level analysis used in this research was group-level analysis. The data collection used in this research is a document analysis method and interviews by email. This research shows the Ocean Cleanup's efforts in partnering with different partners in overcoming plastic waste pollution and cleaning the waste in GPGP. The efforts are believed to be useful since they are able to capture the plastic waste in GPGP and reduce the amount of plastic flowing through rivers. Keywords: The Ocean Cleanup, Environmental NGO, NGO Roles, Plastic Waste